Pengaruh Prinsip-Prinsip Good Governance terhadap Pengelolaan Dana Desa di Desa Medalem - Wahyu Susilo, Toni; Andhaniwati, Erry (Al-Buhuts, 2024)
This study aims to determine the impact of accountability, transparency, and community participation on the management of village funds in Medalem Village, Kradenan District, Blora Regency. This research employs a quantitative method with a population comprising all village residents, totaling 2,553 individuals. The sample was selected using purposive sampling with specific criteria, resulting in 97 respondents. Primary data were collected directly through questionnaires and analyzed using multiple linear regression with SPSS version 25. The findings indicate that accountability and community participation influence the management of village funds, while transparency does not have a significant impact. One of the challenges identified is the lack of openness from the village government to the public. It is recommended that the village government continue to enhance accountable, transparent, and participative management of village funds to improve the overall management in Medalem Village